High school students' grip on life and education: High school students' self-administered work with a life mastering method. Issue 4 (1st October 2020) - Bertelsen, Preben; Ozer, Simon; Faber, Peter; Jacobsen, Anne Sofie; Lund-Laursen, Toke
Abstract: The school system increasingly focuses on the students' grip on life challenges in general. In this article, a life-psychological approach to the development of a general grip on life is tested. The method can be implemented in schools, such as public schools, in high school, as well as in youth education programs. Such implementations can often be organizationally and financially costly, which is why the applicability of the method is tested as a cost-neutral, self-administered method among high school students. The results show that the life-psychological method and its tools can be successfully implemented in a self-administered way regarding development of a good grip on life and its challenges.